Clinical Reasoning: A 6-Year-Old Girl With Right-Sided Pain and Weakness. (10th January 2023) - Gaudioso, Cristina M.; Zolno, Rachel; Wagner, Anne; Mar, Soe
Abstract : We outline the case of a 6-year-old girl presenting with a 2-week course of waxing and waning neurologic symptoms, including right-sided pain, weakness, dizziness, and difficulty walking. Her examination was notable for right-sided weakness, hyperreflexia, and dysmetria. Diagnostic evaluation was significant for MRI with numerous T2 hyperintense, T1 hypointense, and T1-enhancing lesions located in the juxtacortical and periventricular regions, corpus callosum, brainstem, and spinal cord; positive CSF oligoclonal bands; negative serum aquaporin-4 immunoglobulin G (IgG) and myelin oligodendrocyte glycoprotein IgG; and positive serum Epstein-Barr viral capsid antigen IgG.